Esoteric Dimensions of Prayer Worship and Its Implications Against the Development of Social Ethics - T. Faizin (Raudhatun Najah Publisher, 2022)
Prayer is an ubudiyah activity that also has something to do with tasawwuf, which contains the human esoteric dimension. Many lessons and secrets are held in prayer services, especially regarding their implications for the development of social ethics so that the perpetrators are more motivated to have good morals. The methodology used in this study is quantitative with a descriptive analysis approach, research findings, esoteric dimension of prayer worship that is formed closer to Allah strengthens the soul, avoids bad deeds, discipline in life, and creates positive, trustworthy, and honest things; as for the implications, training to regulate order in society strengthens a sense of togetherness, develop bonds of brotherhood and social solidarity.